Drosophila melanogaster primary cell cultures as tools for neurobiology: focusing on mitochondria and Alzheimer\'s disease - Lopes, Caio Fábio Baêta (2023)
Brains are the most complex known objects of universe. Such a complexity emerges from structure and connectivity between neurons, their main building blocks. These are high polarized cells, shaped to capture, to process and to convey electrical stimuli via synapses, orchestrating uncountable discrete signals that give rise to sophisticated phenomena, as consciousness. Neurodegenerative diseases are a set of devastating brain affections that course with neuronal senescence and death. Alzheimer\'s disease (AD), the leading cause of senile dementia worldwide, is a neurodegenerative disease characterized by progessive loss of cogniton and higher functions, due to diffuse central neurotoxicity, putatively attributed to senile plaques, composed of toxic amyloid peptides. Here I introduce a new, innovative, in vitro model for AD, based on third instar Drosophila melanogaster larval brains. The model proved adequate for live cell imaging, using fluorescent probes that allowed membrane, nuclear, mitochondrial and lysosomal stainings. Moreover, results obtained were robust and reproducible. Morphometric data indicate that amyloid missexpression in neurons lead to distinct structural phenotypes on the observed cells, leveraging potential uses of the model.